Consolidamento del concetto di soluzione attraverso un’esperienza laboratoriale - Toncelli, Fabiola; Nocchi, Patrizia; Volpi, Massimiliano (Chimica nella Scuola, 2024)
The students of two classes of a scientific high school have been working on a project whose aim was to make them fully understand the fundamental ideas of solution and of other new chemical concepts. The students had to reflect on a question posed by their teachers: why any limoncello is always murky. To find an answer, they took advantage of their teacher’s theoretical explanations, read books and used a laboratory approach which led them to be engaged in practical activities. Since the idea of this project was born in 2020 and went on in the years following, its side purpose was to help pupils restore those social relationships the COVID-19 pandemic had undermined. Each part of the whole project has been carried out bearing in mind the following distinctive sequence: observation - individual verbalization - collective verbalization - shared conclusion.